Descriptive epidemiology of domain-specific sitting in working adults: the Stormont Study - Clemes, Stacy; Houdmont, Jonathan; Munir, Fehmidah; Wilson, Kelly; Kerr, Robert; Addley, Ken (Oxford University Press, 2016)
Background Given links between sedentary behaviour and unfavourable health outcomes, there is a need to understand the influence of socio-demographic factors on sedentary behaviour to inform effective interventions. This study examined domain-specific sitting times reported across socio-demographic groups of office workers. Methods The analyses are cross-sectional and based on a survey conducted within the Stormont Study, which is tracking employees in the Northern Ireland Civil Service. Participants self-reported their daily sitting times across multiple domains (work, TV, travel, PC use and leisure) on workdays and non-workdays, along with their physical activity and socio-demographic variables (sex, age, marital status, BMI, educational attainment and work pattern). Total and domain-specific sitting on workdays and non-workdays were compared across socio-demographic groups using multivariate analyses of covariance. Results Completed responses were obtained from 4436 participants. For the whole sample, total daily sitting times were higher on workdays in comparison to non-workdays (625 ± 168 versus 469 ± 210 min/day, P < 0.001). On workdays and non-workdays, higher sitting times were reported by individuals aged 18–29 years, obese individuals, full-time workers and single/divorced/widowed individuals (P < 0.001). Conclusions Interventions are needed to combat the high levels of sedentary behaviour observed in office workers, particularly among the highlighted demographic groups. Interventions should target workplace and leisure-time sitting.